2004
DOI: 10.1016/j.ejcts.2004.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Change in right ventricular function during off-pump coronary artery bypass graft surgery

Abstract: The displacement of beating heart for positioning during anastomosis of the graft to OM artery caused significant derangement of RV function and decrease in CO. A thermodilution catheter continuously measuring the CO and RVEF was useful to monitor the change in RV function and volume during OPCAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 22 publications
2
26
0
2
Order By: Relevance
“…These studies linked the changes to positive pressure ventilation, cardiopulmonary bypass, systemic inflammation, and increased pulmonary bed vasoconstriction by vasoactive drugs. [23][24][25] These factors are unlikely to be causative in the present findings because they mediate RV dysfunction through cavity dilation, not reduction as we demonstrated. In addition, several studies have demonstrated normalization of pulmonary vascular resistance by 48 hours after surgery, 24,25 and therefore, this would be unlikely to affect RV function 6 days after surgery.…”
Section: Effects Of Cabg On Rv Functionmentioning
confidence: 51%
See 1 more Smart Citation
“…These studies linked the changes to positive pressure ventilation, cardiopulmonary bypass, systemic inflammation, and increased pulmonary bed vasoconstriction by vasoactive drugs. [23][24][25] These factors are unlikely to be causative in the present findings because they mediate RV dysfunction through cavity dilation, not reduction as we demonstrated. In addition, several studies have demonstrated normalization of pulmonary vascular resistance by 48 hours after surgery, 24,25 and therefore, this would be unlikely to affect RV function 6 days after surgery.…”
Section: Effects Of Cabg On Rv Functionmentioning
confidence: 51%
“…Studies that used thermodilution catheters placed in the pulmonary artery to assess RV function also produced inconsistent results between the different surgical techniques (Table 6). 15,16,24 …”
Section: Comparative Studiesmentioning
confidence: 99%
“…All these findings suggest that probably hampered diastolic filling is not the sole cause of hemodynamic compromise during heart displacement and stabilization, and various mechanisms, such as right ventricular failure [13], left ventricular regional wall motion abnormalities Fig. 1.…”
Section: Discussionmentioning
confidence: 98%
“…In regard to CVP, it is generally accepted that hemodynamic deterioration during OPCAB is due to the effect of cardiac displacement and inevitable pressure applied to the heart, both of which can affect ventricular function and coronary artery blood fl ow during anastomoses of the right coronary artery (RCA) or CX [23][24][25]. Kwak and colleagues [26] demonstrated that significantly reduced right ventricular ejection fraction accompanied by an increase of right ventricle afterload and decreased cardiac index (CI) were observed during heart displacement. Mathison and colleagues [27] suggested that increasing right ventricle end-diastolic pressure as a result of cardiac displacement was the major cause of hemodynamic change during OPCAB.…”
Section: Discussionmentioning
confidence: 99%